Higher chromatic rendition with Cr3+-doped yellow Y3Al5O12:Ce3+ for double-layer remote phosphor white-light-emitting diodes - Dieu An Nguyen Thi; Phuc Dang Huu; Thuy Hang Nguyen Thi (Institute of Advanced Engineering and Science, 2022)
Remote phosphor designs of white-light-emitting diodes (WLEDs) have been recognized for their high thermal stability and excellent luminous efficiency but not for the chromatic rendering. The study presents an approach for the remote phosphor structure to overcome the low-color-rendering issue by enriching its red-light spectral intensity through co-doping Cr3+ and Ce3+ ions into the yellow Y3Al5O12 (YAG) phosphor compound. This ion co-doping process probably enhances emission spectra in the far-red range because of the energy transfer of the integrated ions: Ce3+ Cr3+. Additionally, the luminescence and color properties of the phosphor layer significantly depend on the doped concentration of the Cr3+ ion. Here, with 0.008% Cr3+ in the phosphor composite, either internal or external quantum performances of the dual-layer WLED light are enhanced, which achieved the number of 58.9% and 46.7%, respectively. The color rendering index (CRI) would also be higher if Cr3+ is added, about 77.9, compared to the CRI of 63.2 when using the original YAG:Ce3+ phosphor layer.